Annual report of the Australian Meningococcal Surveillance Programme, 2000 - Tapsall, John; Tapsall, Australian Meningococcal Surveillance Programme (Communicable Diseases Intelligence, 2001)
The National Neisseria Network has undertaken meningococcal isolate surveillance by means of a collaborative laboratory based initiative since 1994. The phenotype (serogroup, serotype and serosubtype) and antibiotic susceptibility of 388 isolates of Neisseria meningitidis from invasive cases of meningococcal disease were determined in 2000. More than 90 per cent of the invasive isolates were either serogroup B or C. There was however, considerable diversity in the phenotypes circulating in the different States and Territories. Serogroup B strains predominated in all jurisdictions except Victoria and were isolated from sporadic cases of invasive disease. Serogroup B phenotypes were generally disparate although phenotypes B:15:P1.7 and B:4:P1.4 were widely distributed. The latter remained especially prominent in New South Wales. The number and proportion of serogroup C isolates again increased in Victoria compared with previous years. Infections with a novel phenotype that was first noted in 1999, C:2a:P1.4(7), were common in Victoria, especially in adolescents and adults, but rarely seen elsewhere in Australia. Phenotype C:2a:P1.2, was also noted in the preceding year and continued to be seen in Victoria in 2000 but was infrequently encountered in other jurisdictions. Serogroup C infections remained common in New South Wales where phenotype C:2a:P1.5 was regularly isolated. About two thirds of all isolates showed decreased susceptibility to the penicillin group of antibiotics (MIC 0.06 to 0.5 mg/L). All isolates tested were susceptible to third generation cephalosporins and to the prophylactic agents rifampicin and ciprofloxacin. Data relating to 147 laboratory-confirmed but culture-negative cases, supplemented information on culture-confirmed cases in this report. Some differences in the patterns of disease were revealed when culture-based and non-culture-based data were compared. Commun Dis Intell 2001;25:113-121.